Contribution to the knowledge of Chinese Gryllacrididae (Orthoptera) XI: Three new species of Homogryllacris from Yunnan Province - Lu, Xiangyi; Zhang, Qianwen; Bian, Xun (Zootaxa, 2022)
This paper reports three new micropterous species of Homogryllacris from Yunnan Province. And we supplement the additional description for Homogryllacris anelytra Shi, Guo & Bian, 2012 and Homogryllacris bilobus (Bey-Bienko, 1957). All examined specimens are deposited in Guangxi Normal University.